Evaluating the impact of heat stress as measured by temperature- humidity index (THI) on test-day milk yield of dairy cattle in Tanzania - Ekine-Dzivenu, Chinyere C.; Mrode, Raphael A.; Ojango, Julie M.K.; Okeyo Mwai, Ally (2019)
The aim of this study was to measure losses in milk production due to the impact of heat stress, using temperature-humidity index (THI) on test-day milk records of small holder dairy cattle farms in Tanzania. Climate data obtained from aWhere, an agricultural weather data platform (http://www.awhere.com) was analysed with 11589 first lactation test day milk records of 2824 dairy cows collected between 2017 and 2018. THI was calculated from daily maximal temperatures and daily minimum humidity. Two multiple linear regression models were fitted with THI treated as a continuous variable to determine the change in test day milk yield in response to THI, and as a categorical variable, grouped into 5 classes (THI1=[63,67.5], THI2 =[67.5,72], THI3 = [72,76.6], THI4= [76.6,81.1], THI5=[81.1,85.6]), to identify THI thresholds for defining comfort zones of the animals. Both models included age at calving, days in milk, breed and herd year season as fixed effects. The results showed a significant (P = 0.02) effect of heat stress on test day milk yield. Milk yield decreased by 0.05 litres per cow per day for each point increase in THI. Significant decrease in daily milk production was observed for the following THI categories: THI2 (-0.69 litres, P=0.03), THI3 (-0.90 litres, P=0.006) and THI4(-0.99 litres, P=0.005) but not for THI5 ( -0.029 litres, P=0.648). This suggests that with THI values above 67.5, the dairy cows in Tanzania will experience temperature related discomfort and heat stress. To mitigate the impact that heat stress induced milk loss has on the income of small holder dairy farmers, especially in the face of a growing climate change threat, breeding strategies such as genomic selection can be explored to identify superior sires more resistant to heat stress for breeding heat tolerant dairy cattle.